Advances in Cryptology - ASIACRYPT 2010 16th International Conference on the Theory and Application of Cryptology and Information Security, Singapore, December 5-9, 2010. Proceedings - Abe, Masayuki; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 16th International Conference on the Theory and Application of Cryptology and Information Security, ASIACRYPT 2010, held in Singapore, in December 2010. The 35 revised full papers presented were carefully reviewed and selected from 216 submissions. The papers are organized in topical sections on hash attacks; symmetric-key cryptosystems; block and stream ciphers; protocols; key exchange; foundation; zero-knowledge; lattice-based cryptography; secure communication and computation; models, notions, and assumptions; and public-key encryption.
Hash Attacks -- Rotational Rebound Attacks on Reduced Skein -- Finding Second Preimages of Short Messages for Hamsi-256 -- Non-full-active Super-Sbox Analysis: Applications to ECHO and Grøstl -- Advanced Meet-in-the-Middle Preimage Attacks: First Results on Full Tiger, and Improved Results on MD4 and SHA-2 -- Collision Attacks against the Knudsen-Preneel Compression Functions -- Symmetric-Key Cryptosystems -- Improved Generic Attacks on Unbalanced Feistel Schemes with Expanding Functions -- The World Is Not Enough: Another Look on Second-Order DPA -- Block and Stream Ciphers -- Conditional Differential Cryptanalysis of NLFSR-Based Cryptosystems -- A Byte-Based Guess and Determine Attack on SOSEMANUK -- Improved Single-Key Attacks on 8-Round AES-192 and AES-256 -- Protocols -- Constant-Size Commitments to Polynomials and Their Applications -- Computationally Secure Pattern Matching in the Presence of Malicious Adversaries -- Linear-Complexity Private Set Intersection Protocols Secure in Malicious Model -- Key Exchange -- Generic Compilers for Authenticated Key Exchange -- A Forward-Secure Symmetric-Key Derivation Protocol -- Foundation -- Efficient String-Commitment from Weak Bit-Commitment -- On the Static Diffie-Hellman Problem on Elliptic Curves over Extension Fields -- Random Oracles with(out) Programmability -- Zero-Knowledge -- Short Pairing-Based Non-interactive Zero-Knowledge Arguments -- Short Non-interactive Zero-Knowledge Proofs -- Optimistic Concurrent Zero Knowledge -- Lattice-Based Cryptography -- Faster Fully Homomorphic Encryption -- A Group Signature Scheme from Lattice Assumptions -- Lattice-Based Blind Signatures -- Secure Communication and Computation -- The Round Complexity of Verifiable Secret Sharing: The Statistical Case -- General Perfectly Secure Message Transmission Using Linear Codes -- On Invertible Sampling and Adaptive Security -- Multiparty Computation for Modulo Reduction without Bit-Decomposition and a Generalization to Bit-Decomposition -- Models, Notions, and Assumptions -- A Closer Look at Anonymity and Robustness in Encryption Schemes -- Limitations on Transformations from Composite-Order to Prime-Order Groups: The Case of Round-Optimal Blind Signatures -- The Semi-Generic Group Model and Applications to Pairing-Based Cryptography -- Public-Key Encryption -- The Degree of Regularity of HFE Systems -- Structured Encryption and Controlled Disclosure -- Leakage Resilient ElGamal Encryption -- Efficient Public-Key Cryptography in the Presence of Key Leakage.
Keywords: Computer science; Data protection; Data encryption (Computer science).; Computer software; Computational complexity; Information Systems; Mathematics; Computer Science; Data Encryption; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Discrete Mathematics in Computer Science; Systems and Data Security; Applications of Mathematics